The relationship between talent identification testing parameters and performance in elite junior swimmers. Issue 12 (December 2018) - Mitchell, Lachlan J.G.; Rattray, Ben; Saunders, Philo U.; Pyne, David B.
Abstract: Objectives: In elite age-group swimming it is unclear to what degree common assessments of anthropometric, jump performance and front-crawl critical speed (CS) correlate with competition performance. Design: Cross-sectional field study. Methods: Forty eight elite national-level junior swimmers (22 males, age 16.5 ± 1.2 y, 26 females, age 15.5 ± 1.1 y; mean ± SD) completed anthropometry tests, loaded and unloaded countermovement jumps and a series of front-crawl time-trials to determine CS and supra-CS distance capacity (D'). Years from peak height velocity (PHV) predicted from anthropometric data was used as a maturity indicator. Race performances within 3 months of testing were standardised to compare across distances and strokes. Multiple linear regression models were formulated using these data. Results: Loaded jump height, mass, D', PHV and humerus breadth best predicted 100 m performance in males (R 2 Adj  = 0.88, p < 0.001), while loaded jump height, chest depth and sitting height predicted female 100 m performances (R 2 Adj  = 0.74, p = 0.002). Loaded and unloaded jump height, mass, CS and PHV (R 2 Adj  = 0.73, p = 0.003) and CS and chest depth (R 2 Adj  = 0.33, p = 0.03) predicted 200 m performance in males and females respectively. Conclusions: Common assessments of power and aerobic capacity in elite junior swimmers explain more variance in competition performance for male than female swimmers, as well as for 100 m rather than 200 m events. These findings highlight the need to empirically assess testing regimens and suggest new tests in this population may be required.